Rodent models of postherpetic neuralgia: How far have we reached? - Ou, Mingxi; Chen, Jiamin; Yang, Shaomin; Xiao, Lizu; Xiong, Donglin; Wu, Songbin (Frontiers in Immunology, 2023)
Background: Induced by varicella zoster virus (VZV), postherpetic neuralgia (PHN) is one of the common complications of herpes zoster (HZ) with refractory pain. Animal models play pivotal roles in disclosing the pain mechanisms and developing effective treatments. However, only a few rodent models focus on the VZV-associated pain and PHN. Objective: To summarize the establishment and characteristics of popular PHN rodent models, thus offer bases for the selection and improvement of PHN models. Design: In this review, we retrospect two promising PHN rodent models, VZV-induced PHN model and HSV1-induced PHN model in terms of pain-related evaluations, their contributions to PHN pathogenesis and pharmacology. Results: 1) Significant difference of two PHN models is the probability of virus proliferation; 2) Most commonly used pain evaluation of PHN model is mechanical allodynia, but pain-induced anxiety and other behaviours are worth noting; 3) From current PHN models, pain mechanisms involve changes in virus gene and host gene expression, neuroimmune–glia interactions and ion channels; 4) antiviral drugs and classical analgesics serve more on the acute stage of herpetic pain. Conclusions: Different PHN models assessed by various pain evaluations combine to fulfil more comprehensive understanding of PHN.